Pengaruh Brand Image, Kualitas Produk Dan Digital Marketing Terhadap Niat Membeli Produk Kecantikan Mop Beauty Oleh Tasya Farasya (Studi Kasus Di Malang) - Nasrifa, Devi Asah; Basalamah, Muhammad Ridwan; Rahmawati, Rahmawati (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract In this period of globalization, each company is confronted with strongly commerce competition within the advanced world. Trade individuals must compete to win commerce competition through the progressively growing computerized world. The expanding concentrated and number of competitors places requests on trade individuals to meet customer desires and wants. The important thing that has to be considered in arrange to win the competition is to supply value and satisfaction to buyers by conveying quality items and administrations at the correct cost. To attain this, it can be done through advanced showcasing as a way to keep up with current advancements so that items are increasingly known to the wider community. This company's commerce technique is anticipated to have an affect on money related and non-financial benefits, survival within the industry, and to attain the organization's long-term objectives  Keywords: Brand Image, Kualitas Produk, Digital Marketing, Minat Beli